The method of preliminary localization of source of excessive air pollution to increase effectiveness of environmental monitoring and supervision in Russia - L. O. Shtripling; V. V. Bazhenov; Yu. V. Kalinin; N. S. Bazhenova; V. V. Merkulov (Омский научный вестник)
The problem of air pollution is raised in many cities, despite developing environmental legislation and the introduction of more environmentally friendly and efficient equipment at industrial enterprises. The main problem is reduced to the localization of the source of pollution, emissions of which have led to a violation of the quality of atmospheric air. Our research is aimed at localizing the area of location of the source of excessive pollution and its identification as soon as possible. The paper presents an algorithm for the preliminary assessment of the location of pollution sources, emissions of which could lead to an excess of permissible concentrations in the air. The results can be used in the work of public authorities in the field of environmental protection.